The Strategy of Organic Pest Control in Ecuador: Capture Effectiveness of Fruit Fly (Anastrepha) Species in Orange Tree Regulated by Volatile Alimentary Attractants - Ganchozo-Mendoza, Enny; Villamar-Torres, Ronald; Molina-Villamar, Jhon; Garcia Cruzaty, Luz Cecilia; Herrera Torres, Jefferson; Martinez-Chevez, Malena; Mehdi Jazayeri, Seyed; Muñoz-Rengifo, Julio; Intriago-Quintana, José Andrés; Segura-Chávez, Edison (AGRIVITA, Journal of Agricultural Science, 2018)
The fruit fly (Diptera: Tephritoidea) is a pest with high phytosanitary impacts and economic importance worldwide. In Ecuador, fruit fly causes significant losses affecting more than 260 different fruit types. This study was aimed to estimate fruit fly capture effectiveness in orange tree regulated by volatile alimentary attractants to propose an alternative biological control. The experimental unit constituted by a Multilure trap (McPhail plastic wet version) for each vegetable attractant. Five volatile alimentary attractants more one control were compared. Thirty-five fruit fly individuals were captured, corresponding to the species Anastrepha obliqua, A. fraterculus, A. striata, and A. leptozona. The most abundant species was A. obliqua with 14 individuals. The most effective treatment was guava juice covering 40 % of the total captured flies. Maximum MTD rate (flies/trap/day) was not significant, considering it as a low catch rate plague. The results indicated the possibility of using this organic control method for fruit fly. It can become one of the technologies as an environmentally friendly method and in favour of farmers' health.